Low-cost protected cultivation – an ideal technology for enhancing capsicum and tomato yield - Chaurasia, S.N. S.; Singh, Raghwendra; Bahadur, Anant; Singh, D. K.; Singh, Sudhir; Koley, T. K; Ram, K.; Saha, S.; Prasad, R. N.; Singh, B. (Indian Horticulture, 2019)
Due to increase in population, rapid urbanization, industrialization and shrinking land holdings, there is tremendous pressure on availability of land resources for agriculture, which results in decreased arable land area year after year. The huge gap between present production and future requirements necessitates intensive vegetable production and availability at affordable prices. Vegetable production can be enhanced by increasing productivity, use of improved cultivars and agro-techniques, bringing additional land under vegetable crops or by promotion of protected cultivation. By adapting protected cultivation, year round availability of quality produce both for domestic use and export, can be assured.